Kant and the Reach of Reason : Studies in Kant's Theory of Rational Systematization - Rescher, Nicholas (Cambridge : Cambridge University Press, 2000)
The essays collected in this volume have a strong thematic and interpretative unity. Their underlying concern is with the overall nature of Kant's philosophical system, and thus with his deepest intentions and basic commitments. The book falls into three parts. The first three essays deal with Kant's approach to things in themselves and with the realm of noumenal causality. The second part considers Kant's approach to the methodology of rational inquiry, and, in particular, his views on cognitive systematization and the limits of philosophizing itself. The third section focuses on the role played by the categorical imperative in both the theoretical and practical philosophy. The aim throughout, one that many Kant scholars and students will find provocative, is to show that in an important sense Kant is prepared to assert the primacy of practical over theoretical philosophy.
Title from publisher's bibliographic system (viewed on 15 Oct 2018).
Keywords: Spectral theory (Mathematics); Mathematical physics